PERANAN RETRIBUSI PASAR DAN JUMLAH PENDUDUK TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) - Syahrain, Ruliyanto (Jurnal Akrab Juara, 2019)
This study aims to examine the role of market levies and population on increasing local own-source revenue (PAD). This study uses secondary data from the regional revenue service (Dispenda) and the central statistical agency (BPS) data collected includes data on market levies, population numbers and the level of local revenue. The analytical method uses the multiple linear regression equation model. The results of this study amounted to one variable that had a positive effect on the increase in population. As for those who did not have a significant effect on the increase in local revenue, namely market fees.